B‐Mode and Doppler Sonography of the Mammary Glands in Dairy Goats for Mastitis Diagnosis. Issue 2 (20th January 2015) - Santos, VJC; Simplício, K; Sanchez, D; Coutinho, L; Teixeira, P; Barros, F; Almeida, V; Rodrigues, L; Bartlewski, P; Oliveira, M; Feliciano, M; Vicente, W
Contents: This study aimed to evaluate the sonographic characteristics of the udder and teats and to determine the Doppler indexes of mammary artery in healthy and undergoing subclinical and clinical mastitis goats. Thirty animals among Saanen and Alpine Brown goats were arranged in three groups, healthy goats (HG), goats with subclinical mastitis (SMG) and goats with clinical mastitis (CMG). Using the B‐mode, the sonographic characteristics (echotexture and echogenicity) and biometry (diameter and area of the udder cistern, diameter and area of the teat cistern and thickness of the teat wall) were evaluated. Using Doppler ultrasonography, the vascular indexes of the mammary artery were obtained. It was observed hyperechogenicity with solid component in the gland cistern when comparing animals with clinical mastitis and healthy mammary tissue. Regarding the echotexture of the breast tissue, there was heterogeneity in the mammary parenchyma on the three groups, for the milk, it was observed homogeneity for animals on HG and SMG and heterogeneity for animals on CMG. Grey‐scale quantitative assessment revealed increase in echogenicity (mean value) for all the structures when comparing the three groups. Biometry did not reveal statistical difference between groups, for none of the evaluated structures. Doppler examination of the mammary artery showed the decrease of end diastolic velocity and raise of pulsatility index between groups. The association of B‐mode and Doppler ultrasonography is useful for the evaluation of the udder of dairy goats with mastitis. It is a sensitive and specific method for the study of this disease. Doppler mode was unable to establish reliable criteria for diagnosis of subclinical mastitis. Moreover, the quantification of echogenicity is a useful technique for the evaluation of the milk in animals with mastitis; therefore, it is suggested that it can be used as complementary technique for the diagnosis of mastitis in goats.